Penyingkiran Pepejal Terampai, Kekeruhan, Aluminium, pH Dan Warna Menggunakan Sistem Pengapungan Udara Terlarut - Md Darom, Mohd Afizul (Universiti Sains Malaysia, 2006)
Dissolved air floatation (DAF) is a process of solid-liquid separation used in the water treatment process. This method is the alternative method to sedimentation process in conventional system. The objectives of this study are to identify the efficiency of dissolved air floatation process in solid-liquid separation in removing selected water quality parameter such as suspended solid (SS), turbidity, residual aluminium, pH and color. The efficiency of this process is to be determined by checking the quality of the selected parameter in the effluent of the pilot plant using DAF. The values of the result are compared to the raw water quality and the National Standard of Drinking Safety by Ministry of Health (MOH) and World Health Organization (WHO). Generally, from this study the efficiency of the DAF system at the pilot plant indicate the removal of suspended solid is 91.67 to 98.59 percent, turbidity removal is 67.11 to 95.67 percent and color removal is 91.67 to 98.00 percent. There are no standardisation for the value of floatation pH but it will be used as the guidance for the next stage of water treatment. In this study, the value of the residual aluminium in the DAF effluent is larger than the aluminium content in raw water. The residual aluminium increase because of the problem in the aluminium sulphate dosing in the coagulation process.